Alcohol, tobacco and breast cancer: should alcohol be condemned and tobacco acquitted? - Silva, I dos Santos (Nature Publishing Group, 2002)
British Journal of Cancer (2002) 87, 1195–1196. doi:10.1038/sj.bjc.6600633 www.bjcancer.com © 2002 Cancer Research UK